National Postpartum Permanent Contraception Practices and Perceived Barriers - Murphy, Ellen; Pelletier, Andrea; Fay, Kathryn; Bartz, Deborah (Obstetrics and gynecology (New York. 1953), 2024)
Single institution-level studies have demonstrated low postpartum permanent contraception fulfillment rates after vaginal birth. To explore the national scope of the problem, we collected cross-sectional survey data from faculty at 109 U.S. academic medical centers to elicit perceptions about postpartum permanent contraception practices after vaginal birth, including barriers to and changes in practice after the Dobbs v Jackson Women's Health Organization decision, a decision that eliminated the U.S. federal protection of the right to abortion. Of 68 respondent institutions, 65 (95.6%) offered postpartum permanent contraception. A large majority (87.3%) perceived there to be a problem with postpartum permanent contraception fulfillment at their institution. Respondents at institutions with postpartum permanent contraception fulfillment rates in the bottom quartile used main operating rooms (66.7% vs 25.0% respectively, P =.032) and reported institutional culture barriers (86.7% vs 50.0%, respectively, P =.054) more frequently than respondents in the top quartile. Our national data indicate that health care culture changes and the use of labor and delivery operating rooms could increase postpartum permanent contraception fulfillment.